Low‐noise tunable filter design by means of active components. Issue 1 (1st January 2016) - Pantoli, L.; Stornelli, V.; Leuzzi, G.
Abstract : A low‐noise tunable filter with high dynamic range and minimum power consumption is presented and addressed with circuit details. It is based on an active solution simulating an inductive behaviour that allows improving the filter quality factor without affecting the noise performance. The low‐order bandpass filter is realised with minimum number of components and it is suitable to be integrated in integrated circuit or used in hybrid transceiver and modern reconfigurable radio systems. A prototype board with discrete components has been fabricated and tested with good results.